Mass casualty incidents during the ten years of telemedical maritime assistance service in Gdynia, Poland - Przemysław Paul; Angelika Rucińska; Lukáš Páleníček; Joanna Szafran-Dobrowolska; Marcin Renke (Nofer Institute of Occupational Medicine, 2023)
Mass casualty incident (MCI) is one of the most difficult situation in emergency medicine. Due to the specific conditions, MCIs occurring at sea are usually far more demanding than those happening on land. In this paper the authors would like to describe the MCIs, which have happened during almost 10 years of functioning of the Polish Telemedical Maritime Assistance Service (TMAS). First incident concerned a group of migrants floating on a raft on the Gulf of Mexico. The cause of the second incident was acute organophosphate intoxication among the crew of the merchant ship. The third incident was triggered by the coronavirus disease 2019 (COVID-19). It is important to emphasize, that triage system may help in proper management of MCIs. Cooperation of the medical services, such as TMAS, local emergency medical staff, Search and Rescue (SAR) service and military force seems to be crucial in MCI managements occuring at sea. In case of any doubts, change of a course and heading to the nearest port or immediate evacuation should be taken into consideration. The authors believe that analysis of these incidents may help TMAS personnel all over the world to handle MCIs in the future. Med Pr. 2023;74(2):145-50